HUBUNGAN PENGETAHUAN MAHASISWI DAN DUKUNGAN ORANG TUA DENGAN PERILAKU MAHASISWI UNTUK MELAKUKAN KEBERSIHAN ORGAN REPRODUKSI DI AKADEMI KEPERAWATAN HERMINA MANGGALA HUSADA TAHUN 2019 - Junita Maratur Silitonga, Ria Anugrahwati (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2019)
Adolescent reproductive health depends on adolescent knowledge about how to care for the reproductive organs, the participation of parents in providing information about cleanliness of the reproductive organs, this study aims to relate the knowledge of adolescent girls and support parents with student behavior to perform hygiene of reproductive organs at the Hermina Nursing Academy Manggala Husada. This study uses a descriptive correlation research design that is research conducted to see the relationship between the independent and dependent variables. This study uses a non-experimental quantitative method with a cross-sectional approach. The sample in this study were 67 first-rate female students. Data collection using a questionnaire. Analysis of the data used chi-square test. The result showed that respondents who had good knowledge were 47 respondents (70.1%), good parental support as many as 44 respondents (65.7%), and the behavior of adolescent girls to clean the reproductive organs well was 49 respondents ( 73.1%) Indicating that there was a relationship between knowledge and the behavior of adolescent girls to clean the reproductive organs (p value < ?), means that there was the relationship between parental support and the behavior of adolescent girls to clean the reproductive organs. It is expected that parents who have teenage girls can play an active role in providing information and education on how to maintain the cleanliness of the reproductive organs